Building a free open source based automated system administration multi-threading and parallel programming performance - Wani, Sharyar; M.H Henchiri, Mourad (IJEAIS, 2020)
Building a system integrates the thoughts of security related issues and raises the concerns about the environment compatibility in order to provide secured environments. Administrating tasks stand behind complex dashboards and gives a view to all theoretical skills on field. Yet, limitations caused by constraints are faced, and to trespass those is a must through many different feasible ways; mainly the FOSS (Free Open Source Software) is a key for plenty of Information Technology security and also administration issues. This research covers specific outcomes to fulfill systems administration expertise along with the necessary security requirements.